Views of Hungarian Historiography on the Question of the Arrival of Magyars in the Carpathian Basin and Their Relations to the Surroundings (From the Middle of the 19th Century to the End of the 20th Century) - Pintérová , Beáta (Dějiny – teorie – kritika, 2011)
The end of Great Moravia, or the question of its existence, played a significant role in the history of the Slovaks from the end of the eighteenth century ( Juraj Papánek) and its political history is a component of the syntheses of the history of Slovakia to this day. The this days of Great Moravia belong to the period when a new ethic group – Magyars – appeared in the Carpathian Basin. Historians in the nineteenth century called this process occupation of the homeland (honfoglalás). This historical moment gradually became the subject of sundry myths. In Slovak historiography, two theories have been created: hospitable (it speaks of the hospitable acceptance of the Magyars by the Slavs, or the Slovaks), and subjugation (it speaks of the violent subjugation of the Slavs, or Slovaks, by the Magyars). In her study, the author focused on an analysis of the issue of occupation of the homeland, the relations of the Magyars to the local population, the formation of Hungarian statehood and the acceptance of Christianity in the works of the most important Hungarian historians of the nineteenth and predominantly the twentieth centuries (Mihály Horváth, Károly Szabó, Gyula Pauler, János Karácsonyi, Bálint Hóman, Gyula Németh, Erik Molnár, Gyula Moravcsik, György Györ y and Gyula Kristó), with an emphasis on the differences in their approaches and interpretations.